Not all flowers' visitors are pollinators: Combining indicators to identify their role in the cocoa pollination service - Isabelle Merle; Jimmy Trinidad Pico Rosado; Nelly Judith Paredes Andrade; Xavier Argout; Fabrice Requier (Agriculture, Ecosystems & Environment, 2025)

Bee and non-bee pollinator importance for local food security - Fabrice Requier; Nestor Pérez-Méndez; Georg K.S. Andersson; Elsa Blareau; Isabelle Merle; Lucas A. Garibaldi (Trends in Ecology & Evolution, 2023)

Staphylococcus capitis isolated from bloodstream infections: a nationwide 3-month survey in 38 neonatal intensive care units - Marie Decalonne; Sandra Dos Santos; Rémi Gimenes; Florent Goube; Géraldine Abadie; Saïd Aberrane; Vanina Ambrogi; Raoul Baron; Patrick Barthelemy; Isabelle Bauvin; Olivier Belmonte; Emilie Benabid; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
To increase the knowledge about S. capitis in the neonatal setting, we conducted a nationwide 3-month survey in 38 neonatal intensive care units (NICUs) covering 56.6% of French NICU beds. We demonstrated 14.2% of S. capitis BSI ( S.cap BSI) among nosocomial BSIs. S.cap BSI incidence rate was 0.59 per 1000 patient-days. A total of 55.0% of the S.cap BSIs were late onset catheter-related BSIs. The S. capitis strains infected preterm babies (median gestational age 26 weeks, median birth weight 855 g). They were resistant to methicillin and aminoglycosides and belonged to the NRCS-A clone. Evolution was favorable in all but one case, following vancomycin treatment.

Production of Two Vaccinating Recombinant Rotavirus Proteins in the Milk of Transgenic Rabbits - Eric Soler; Agnès Le Saux; Frédéric Guinut; Bruno Passet; Ruxandra Cohen; Christine Merle; Annie Charpilienne; Cynthia Fourgeux; Véronique Sorel; Antoine Piriou; Isabelle Schwartz-Cornil; Jean Cohen; et al. (Transgenic Research, 2005)